2015
DOI: 10.1186/s13063-015-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining cognitive bias modification training with motivational support in alcohol dependent outpatients: study protocol for a randomised controlled trial

Abstract: BackgroundAddiction research has hypothesised that automatic and reflective cognitive processes play an important role in the onset and maintenance of alcohol (ab)use, wherein automatic reactions to drug-related cues steer the drug user towards consuming before reflective processes can get over and steer towards a different behavioural response. These automatic processes include the tendency to attend and approach alcohol cues. These biases may be trained away from alcohol via computerised cognitive bias modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…The ABPS (Van Deursen et al., 2013) and its Italian version (Boffo et al., 2015) are currently being used in a cognitive bias measurement and modification study, allowing current findings to be compared with measures of implicit cognition. Furthermore, these studies may answer whether noncontextualized pictures are indeed are most effective to measure and train cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…The ABPS (Van Deursen et al., 2013) and its Italian version (Boffo et al., 2015) are currently being used in a cognitive bias measurement and modification study, allowing current findings to be compared with measures of implicit cognition. Furthermore, these studies may answer whether noncontextualized pictures are indeed are most effective to measure and train cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although unlikely (57), it is possible that a single session of motivational interviewing influenced both baseline measures of bias and washed out the therapeutic effects of ABMT relative to control therapy. Importantly, future studies are needed to determine how different motivational therapies may interact with ABMT (58). Previous research has reported ABMT efficacy with five (21) or fewer (19) brief interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we should perhaps more clearly differentiate between the two aforementioned types of motivation involved in CBM. Besides having a motivation to change one's behavior (e.g., maladaptive substance use), there is a related, but separate, motivation to complete a potentially tedious multi-session training in order to do so (Boffo, Pronk, Wiers, & Mannarini, 2015). While it remains unclear whether one needs both in order for CBM to be effective, participants may still need at least some degree of an intrinsic motivation to change their behavior in order for CBM to have any effect Wiers, Houben, et al, 2015).…”
Section: Critical Notesmentioning
confidence: 97%